2020
DOI: 10.3390/pathogens9030165
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis of Anaplasma Antibody Competitive ELISA Using the ROC Curve for Screening of Anaplasmosis in Camel Populations in Egypt

Abstract: Anaplasmosis is a tick-born and potential zoonotic disease caused by Anaplasma (A.) phagocytophilum, A. ovis, A. platys and A. capra. Anaplasma marginale affecting bovines and camels causing significant economic losses. Camels as an integral part of the socio-economic lifestyle of nomads in semi-arid to arid ecosystems are prone to suffer from subclinical Anaplasma infections. This study aimed to determine the performance and adaptation of commercial competitive Anaplasma ELISA (cELISA) as a tool for screening… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
8
1
1
Order By: Relevance
“…In which n is the sample size, Pexp is the expected prevalence rate and d is precision. The expected prevalence rate that was used in this study was 34.1%, as previously reported by Parvizi et al [4], with a 95% confidence interval and 5% precision. The majority of the study animals were chosen at random from small-scale farmers that keep camels as working animals.…”
Section: Sample Collection and Preparationsupporting
confidence: 68%
See 4 more Smart Citations
“…In which n is the sample size, Pexp is the expected prevalence rate and d is precision. The expected prevalence rate that was used in this study was 34.1%, as previously reported by Parvizi et al [4], with a 95% confidence interval and 5% precision. The majority of the study animals were chosen at random from small-scale farmers that keep camels as working animals.…”
Section: Sample Collection and Preparationsupporting
confidence: 68%
“…In Egypt, recent studies revealed 47.4%, 47.4% and 67.37% prevalence rates of anaplasmosis in camels. These findings were based on tests that employed cELISA, microscopic examination and PCR techniques [3,4]. Other studies conducted in various countries have reported high prevalence rates of 26-95.5%, 34.2%, 39.6% and 61.11% in Saudi Arabia, Iran, Morocco and Niger, respectively [14,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations